Penggunaan Media Sosial sebagai Sarana Promosi Wisata Kota Pagar Alam (Studi Kasus pada Akun Instagram @greenparadise_pga16) - Julianti, Rani; Hamidah; Muslimin (Pubmedia Social Sciences and Humanities, 2024)
The emergence of social media is one of the results of the very rapid development of the internet and technology. Instagram is one of the most popular social media platforms for tourism promotion because it allows the rapid dissemination of information. Green Paradise Tourism is one type of tourism that uses Instagram as a promotional tool. The aim of this research is to find out how managers use social media to promote their tourism, as well as supporting and inhibiting factors in using Instagram. This research uses a qualitative method that uses a descriptive approach. The data collection methods used were interviews, observation and documentation. The research results show that: (1) Instagram is very effective as a promotional platform by using its features such as photo titles or captions, hashtags, Instagram stories, reposts and reels, as well as using the AIDA concept (Attention, Interest, Desire, Action) to attract followers' attention. (2) Factors that support the use of Instagram social media to promote Green Paradise Tourism in Pagar Alam City are promotions using its features such as photo titles or captions. Meanwhile, the inhibiting factors are the content to be posted and promoted as well as competition with destinations, especially with more aggressive promotional tactics or greater attractiveness.